2008
DOI: 10.1002/bies.20784
|View full text |Cite
|
Sign up to set email alerts
|

Tumorigenesis and neurodegeneration: two sides of the same coin?

Abstract: SummaryDysregulation of genes that control cell-cycle progression and DNA repair is a hallmark of tumorigenesis. It is becoming increasingly apparent, however, that these defects also contribute to degeneration of post-mitotic neurons under certain conditions. The gene for ataxiatelangiectasia mutated (ATM) is a prototype for this dual mechanism of action, with loss-of-function mutations causing not only selective degeneration of cerebellar neurons but also increased susceptibility to breast cancer and hematol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
53
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(55 citation statements)
references
References 86 publications
2
53
0
Order By: Relevance
“…However, ablation of parkin expression induced apoptotic cell death in human dopaminergic cells (31). These results suggest that in terminally differentiated cells, including neurons, reactivation of the cell cycle induces apoptosis rather than proliferation (32). Therefore, parkin may exert different effects depending on the cell type and cell cycle status.…”
Section: Discussionmentioning
confidence: 92%
“…However, ablation of parkin expression induced apoptotic cell death in human dopaminergic cells (31). These results suggest that in terminally differentiated cells, including neurons, reactivation of the cell cycle induces apoptosis rather than proliferation (32). Therefore, parkin may exert different effects depending on the cell type and cell cycle status.…”
Section: Discussionmentioning
confidence: 92%
“…In this context, it has been suggested that reentry in the cell cycle, together with oxidative stress production, constitutes a component of the apoptotic cascade in the process of neuronal cell death through the expression of the transcription factor E2F-1 [25,[52][53][54][55][56][57][58]. Currently, the mechanism responsible for cell-cycle activation is unknown and its place in the apoptotic route, prior to the activation of the intrinsic (mitochondrial) programmed cell-death pathway, still requires clarification.…”
Section: Discussionmentioning
confidence: 99%
“…Parkin now seems to be a validated target to modulate autophagy and/or the proteasome, preventing the proliferation of cancer cells [20]. Relevant to cancer, the early transcription factor and key regulator of cell cycle c-Jun [21] interacts with Parkin to prevent neural apoptosis [22]. c-Jun activity (at least in part) is controlled by its interaction with the tumor repressor p53 [23], the dysfunction of which is linked to tumorigenesis [24].…”
Section: Parkin Function In Cancer and Neurodegenerationmentioning
confidence: 99%